1993
DOI: 10.1073/pnas.90.18.8576
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mammalian glutathione S-transferase 5-5 in Salmonella typhimurium TA1535 leads to base-pair mutations upon exposure to dihalomethanes.

Abstract: Dihalomethanes can produce liver tumors in mice but not in rats, and concern exists about the risk of these compounds to humans. Glutathione (GSH) conjugation of dihalomethanes has been considered to be a crifical event in the bioactivation process, and risk assessment is based upon this premise; however, there is little experimental support for this view or information about the basis of genotoxicity. A plasmid vector containing rat GSH S-transferase 5-5 was transfected into the SalmoneUla typhimurium tester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
166
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(178 citation statements)
references
References 38 publications
9
166
0
3
Order By: Relevance
“…DM11 incubated with glutathione and chlorofluoromethane (6). Chemically synthesized S-chloromethylglutathione alkylated deoxyguanosine in vitro (11), and the main product of this reaction was characterized as S-[1-N 2 -deoxyguanosinylmethyl]glutathione (11,44). Nevertheless, the formation of DNA lesions as a consequence of S-chloromethylglutathione formation during conversion of DCM by DCM dehalogenase-GST remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM11 incubated with glutathione and chlorofluoromethane (6). Chemically synthesized S-chloromethylglutathione alkylated deoxyguanosine in vitro (11), and the main product of this reaction was characterized as S-[1-N 2 -deoxyguanosinylmethyl]glutathione (11,44). Nevertheless, the formation of DNA lesions as a consequence of S-chloromethylglutathione formation during conversion of DCM by DCM dehalogenase-GST remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, DCM-converting GSTs from mammals and methylotrophic bacteria have toxic and mutagenic effects in Salmonella enterica serovar Typhimurium (18,44) and Methylobacterium (18). On the other hand, the massive production of hydrochloric acid by cytosolic DCM dehalogenase during growth with DCM suggests that DCM-degrading methylotrophic bacteria may have evolved efficient systems for the maintenance of intracellular pH and for the excretion of chloride ions.…”
mentioning
confidence: 99%
“…In an experimental study, the GSH conjugation of dihalomethanes, such as dichloromethane, which have a similar chemical structure to VCM, has been clearly demonstrated to result in genotoxicity (Thier et al 1993). Garnier et al (1996) reported, after acute inhalation exposure to methyl bromide involving two workers, the GST T1-positive worker showed signs of severe neurotoxicity, whereas the second worker, with GST T1-null genotype, developed only mild neurotoxic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…20 A significant negative interaction was observed between GSTT1 null and lung cancer in occupationally exposed subjects. 12 Speculations as to the mechanism of the protective effect of GSTT1 in human cancer have largely focused on the possibility that the products of GSTT1 conjugating reactions could produce in certain instances more carcinogenic metabolites, such as for the dihalomethanes and other chlorinated hydrocarbons, [21][22][23][24] which are known to be bioactivated by GSTT1. In addition, since the GST genes use certain chemopreventive compounds such as isothiocyanates as substrates, the deletion of GSTT1 could lead to the availability of higher levels of cancer preventing compounds.…”
mentioning
confidence: 99%